Analisis Ketimpangan Pendidikan pada Masa Covid-19 di Nagari Sisawah Kabupaten Sijunjung - Siska, Felia; Rudagi, Reindy (AL MA'ARIEF : Jurnal Pendidikan Sosial dan Budaya, 2021)
The focus of this study is generally analyzing educational inequality in rural or rural areas during COVID-19. Specifically analyze the factors of educational inequality and solutions to overcome the educational inequality of rural areas or the mass country of COVID-19. Research attachment using qualitative research, data collection methods are facilitated from participant observation, in-depth interviews and document data collection. The results of this study showed the factors that caused the inequality of Education in Nagari Sisawah Sijunjung Regency during the Covid-19 period was a). condition of Nagari Sisawah area located in depth, b). Nagari Sisawah is one of the areas that are not reachable by cellular networks and internet networks making it difficult for students to learn online, c). Not all children have school support equipment or media or online lectures, d). The difficulty of determining learning methods for children who attend school in Nagari Sisawah. Solutions to overcome education inequality in Nagari Sisawah Sijunjung district are analyzed from solutions provided by the government, schools and parents who synergize to alleviate educational inequality in Nagari Sisawah during the Covid-19 pandemic so that education continues to be carried out and running well.